Synthesis and Structure of the Sodium Phosphidosilicate Na2SiP2. Issue 7 (6th February 2020) - Haffner, Arthur; Hatz, Anna‐Katharina; Hoch, Constantin; Lotsch, Bettina V.; Johrendt, Dirk
Abstract : Ion conductors of light alkaline metals based on earth‐abundant elements are important components for all‐solid‐state batteries. The new sodium‐rich phosphidosilicate Na2 SiP2 was synthesized by solid state reaction of stoichiometric amounts of the elements at 973 K and characterized by single‐crystal X‐ray diffraction (space group Pccn (no. 56), a = 12.7929(5) Å, b = 22.3109(9) Å, c = 6.0522(2) Å and Z = 16) and solid‐state NMR under MAS conditions. The compound forms dark‐red twinned crystals, and its crystal structure contains edge‐sharing SiP4 tetrahedra connected to infinite ∞ 1 [SiP4/2 ] chains. The sodium ions between the chains are fairly mobile. Electrochemical impedance spectroscopy shows a total ionic conductivity of σ (Na +, 373 K) = 2.3 ? 10 –6 Scm –1 with an activation energy of E a = 0.43 eV, and the galvanostatic polarization reveals mixed conduction behavior with a transference number of 0.8. Abstract : Sodium‐rich phosphidosilicate Na2 SiP2 was discovered and characterized by X‐ray diffraction and solid‐state NMR spectroscopy, revealing fairly mobile sodium ions between anionic ∞ 1 [SiP4/2 ] chains of edge‐condensed SiP4 tetrahedra. Impedance spectroscopy classifies this new material as a sort of mixed ionic electronic conductor.